1995
DOI: 10.1172/jci118007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against either a premature stop codon or the absence of obese gene mRNA in human obesity.

Abstract: Obese (ob) gene expression in abdominal subcutaneous adipocytes from lean and obese humans was examined. The full coding region of the ob gene was isolated from a human adipocyte cDNA library. Translation of the insert confirmed the reported amino acid sequence. There was no difference in the sequence of an reverse transcription PCR product of the coding region from five lean and five obese subjects. The nonsense mutation in the ob mouse which results in the conversion of arginine 105 to a stop codon was not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
218
1
10

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(244 citation statements)
references
References 10 publications
15
218
1
10
Order By: Relevance
“…Leptin causes weight loss in mice by reducing food intake and increasing energy expenditure (2)(3)(4)(5). Furthermore, ob gene expression is increased in human obesity (6)(7)(8)(9) and in various animal models of obesity (10). The accumulated evidence suggests that leptin is important in controlling body weight.…”
mentioning
confidence: 99%
“…Leptin causes weight loss in mice by reducing food intake and increasing energy expenditure (2)(3)(4)(5). Furthermore, ob gene expression is increased in human obesity (6)(7)(8)(9) and in various animal models of obesity (10). The accumulated evidence suggests that leptin is important in controlling body weight.…”
mentioning
confidence: 99%
“…Whereas some progress in treatment of these children with leptin has been reported, treatment of obese subjects without mutations the leptin gene has been less successful. Obese humans actually have elevated rather than decreased levels of leptin suggestive of hormonal resistance analogous to insulin resistance (50) and leptin levels show a strong positive correlation with the total fat mass (51). Moreover, contribution of common variants in the leptin receptor gene to obesity and obesity-related phenotypes including leptin levels has remained more or less elusive.…”
Section: Obesity Genes and Type 2 Diabetesmentioning
confidence: 99%
“…The ob gene has recently been cloned and shown to encode for a 167-amino acid protein, leptin, which is secreted exclusively from the adipocytes of white fat [1][2][3][4][5]. Leptin has been shown to lower body weight by restraining appetite [5][6][7][8] and by altering metabolic processes [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, leptin mRNA levels have been studied in rats with obesity secondary to ventromedial hypothalamic lesions and increase in parallel with body weight [10,11], fulfilling one of the requirement of this regulatory system. Also in humans, it has recently been shown that leptin mRNA levels in white adipocytes increase or decrease in parallel with the body mass index [3,12]. Although believed to be a long-term regulator of body weight, increasing *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%